Implementation of the development of a typical Papuan teacher education college (KPG) curriculum in Merauke district - Elias Esembi (Journal of Education Innovation and Curriculum Development, 2023)
This study aims to determine 1) Implementation of the Papuan Teacher Education College (KPG) Curriculum Development in Merauke; 2) Obstacles in the implementation of the Merauke Papuan Typical Teacher Education College (KPG) curriculum development. (This research was carried out at the Merauke Special KPG Papua Office and School. The main study was centered at the Merauke Papua KPG School). Determination of the sample is done intentionally or purposive sampling, which is a technique of determining the sample with special considerations in accordance with the research objectives. Data analysis was carried out in a qualitative-descriptive manner. The results of the study show that: 1) The implementation of the College Curriculum application system is currently undergoing an improvement process in order to find a form in accordance with the character and local culture of Papua. Although the implementation has not fully met expectations,2) The implementation of the Papuan Teacher Education Curriculum in Merauke faces obstacles, among others related to the lack of facilities and limited human resources, in the management of education.